Goethe, Romanticism and the Anglo-American Critical Tradition - Nicholls, Angus (Romanticism on the Net, 2002)
AbstractThis paper questions the traditional German view that Goethe (1749-1832) was a ‘Classical’ and not a ‘Romantic’ author, by situating his works within the context of the European Romantic movement as it has been theorised in the work of M.H. Abrams. Taking issue with Jerome McGann’s critique of Abrams as outlined in The Romantic Ideology (1983), the paper argues for a partial resuscitation of Abrams’s thesis in Natural Supernaturalism (1971): namely, that Romantic literature and philosophy undertakes a secularisation of Western religious/philosophical thought-systems. Likening Abrams’s sweeping and synthetic approach to the Romantic period to a Kantian ‘Idea of Pure Reason’, the paper contends that broad literary/historical periodisations like that offered in Natural Supernaturalism can still retain a contingent and provisional theoretical utility, particularly in relation to understanding trans-national literary/philosophical movements like Romanticism. Within this argumentative context, Goethe’s works are viewed as being a case in point. Challenging the mainstream German theory that Goethe’s works belong predominantly to two literary movements which existed discretely from the Romantic movement –‘Storm and Stress’ and ‘Weimar Classicism’ – the paper argues that Goethe’s entire oeuvre undertakes a sustained exploration of a philosophical issue which is central to trans-national European Romanticism as characterised by Abrams: the relationship between the human subject and the objects of nature. Works by Goethe considered in the paper include The Sorrows of Young Werther (1774) and the Neo-Kantian scientific essay ‘The Experiment as Mediator between Object and Subject’ (1792).